Antifungal Activity of Rosemary (Rosmarinus officinalis L.) Emulsion Gel Compared to Nystatin on Candida albicans Stored Isolate from HIV/AIDS Patients with Oral Candidiasis - Wardiana, Maya; Astindari; Ervianti, Evy; Afif Nurul Hidayati; Diah Mira Indramaya; Pepy Dwi Endraswari; Budi Utomo; Dwi Murtiastutik (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Oral candidiasis (OC), frequently caused by Candida albicans, is the most common opportunistic infection in HIV/AIDS patients. Topical treatment for OC is limited. In vitro study revealed rosemary (Rosmarinus officinalis L.) essential oil has an antifungal effect. However, the essential oil is volatile and is not recommended to be applied to the skin and mucosa; therefore, emulsion gel (emulgel) is made. Purpose: This study was conducted to evaluate the antifungal activity of rosemary emulgel 6.25%, 25%, 37.5%, and 50% compared to nystatin. Methods: This study is an in vitro test using the disk diffusion method to d etermine the antifungal activity shown by the inhibitory zones of rosemary emulgel at 6.25%, 25%, 37.5%, and 50% compared to nystatin to stored isolates of C. albicans from HIV/AIDS patients with OC. Result: Rosemary emulgel 6.25% dan 25% did not show antifungal activity because no inhibitory zone was shown. The inhibitory zone diameter provided by rosemary emulgel 37.5%; 50%; and nystatin against C. albicans isolates were 3.17±3.763 mm; 7.00±4.107 mm; and 30.13±5.319 mm respectively. Significant differences in antifungal activity were shown by the inhibitory zone diameter provided between rosemary emulgel 37.5%, 50%, and nystatin (p<0,05). Conclusion: Rosemary emulgel 37.5% dan 50% had antifungal activity showed by the formation of inhibitory zone against Candida species isolates in disk diffusion method even though it was weaker compared to nystatin as a standard antifungal.